ETNOFISIKA PADA ALAT MUSIK TRADISONAL SEBAGAI MEDIA PEMBELAJARAN FISIKA DALAM MENIGKATKAN MINAT BELAJAR PESERTA DIDIK - Yusdarina Yusdarina; Nabila Nahda; Syamsuriana Basri; Napsawati Napsawati (CV. ADIBA ASIHA AMIRA, 2024)
This research is a quantitative research with an experimental research method. The design of this research is One-Group Pretest-Posttest Design. The aim is to (1) determine the effect of ethnophysics of traditional musical instruments Gandrang Bulo on sound wave material on the interest in learning physics in class XI students at SMAS Bukit Tinggi (2) To determine the level of interest in learning physics with the application of ethnophysics media of traditional musical instruments Gandrang Bulo on sound wave material in class XI students at SMAS Bukit Tinggi. The subjects of this study were class IX students in the even semester of 2023/2024. This study was conducted in 5 meetings and data collection was carried out using multiple-choice tests that had been tested for validity. The research data were analyzed quantitatively using IBM SPSS Version 29. From the research results, it can be concluded that (1) The description of the level of interest in learning physics with the application of ethnophysical media of the traditional musical instrument Gandrang Bulo on the indicator of feelings of pleasure is in the high category, the attention category is in the low category, while in the interest category it is in the high category. (2) There is an influence of ethnophysics of the traditional musical instrument Gandrang Bulo on the material of sound waves on interest in learning, which can be seen from the average Ngain experiencing an increase in the high level.